Familiarity with Measures to Reduce Administrative Burdens in The Public and Private Sector in Slovenia - Urška Milavec; Maja Klun (Central European Public Administration Review)
Measures to reduce administrative burdens are part of efforts to improve regulation quality. The aim of the research carried out in 2010 in the public and private sector was to determine whether their staff display different levels of familiarity with the measures and whether both sectors define the same groups of regulation as the most burdensome. The results indicated that information provision on measures to reduce administrative burdens in Slovenia is poor, particularly in the private sector, which is intended as the main beneficiary of these measures. Despite this, the private sector reported that regulation for small and medium-sized businesses had improved over the period in which measures to reduce administrative burdens had been implemented. The public sector assessed public procurement regulation as the most burdensome, while the private sector ranked employment regulations as the most burdensome.